EFEKTIVITAS PENGAWASAN PUNGUTAN LIAR DI JEMBATAN TIMBANG - Wibawa, Samodra; F.M, Arya Fauzy; Habibah, Ainun (Jurnal Ilmu Administrasi Negara, 2013)
Bribery or illegal paymentsin the street, especially in the transportation of goods in weighing bridge, is still rampant. This leadto various negative impacts, such as accidents, road damage and loss of the state treasury. Someprovinces have actually set up rules to prevent it, but the Transportation Department Officials didnot implement it properly. This study aims to determine the effectiveness controlling of illegalpayment at weigh stations. The method used in this research is a case study with the object ofstudy illegal payments at weigh Karasidenan Surakarta. Results showed that officers conductedsurveillance on the bridge transportation agencies have not been effective because internal controlsare less well supported by external controls of outside agencies as well as from service users weighbridge itself. The implications of the results of this study suggest the need for cooperation of allparties concerned to work together to comply with rule of Jateng on Control of Goods Transport(No. 1/2012), so rampant illegal payment at weigh stations can be minimized. Key words:illegal payment, outward-looking strategy, inward-looking strategy, effectiveness of controlling.